Digital Analyses of Landsat ETM+ for Identify Agroforestry System in Riau - Nasrul, Besri; Idwar, . (JOURNAL OF TROPICAL SOILS, 2009)
The objectives were to identify land characteristics of agroforestry system that influencing its benefit value, and to compile criteria of site specific. Location were identified by the Landsat 7 ETM+ that designed in the landuse utilization type: rubber agroforestry is identified by cyan old (RGB pixel 143,37; 173,04; 96,03) and palm oil agroforestry is identified by varying bright green-green (red-green-blue pixel 33-145; 142-253; 46-139). In each the landuse utilization type done by measurement of land characteristics, cost the inputs, and price the benefits. The maximum likelihood classification system is used for classification; the benefit value were calculated by benefit-cost ratio; the suitability criteria of site spesific were compiled by cluster analysis. The economic suitability criteria of rubber are: I (4,18-3,94); II (3,94-3,15); III (3,15-2,73); IV (2,73-2,31), the economic suitability criteria of palm oil are: I (3,30-2,72); II (2,72-2,07); III (2,07-1,38); IV (1,38-1,18), and would be base saturation, exchangeable Ca, and Mg. These criteria can be used to evaluate of suitability for the agroforestry system rubber and palm oil in Riau.